Solar charger with solar tracking - Ngoi Kok Kheng (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
This Final Year Project report is about Solar Charger with Solar Tracking System. Nowadays, solar energy is the most popular renewable energy used as its most sustainable energy source which is not substantially depleted and does not entail any significant pollutant emissions or the environmental problems. The continuing use of fossil fuels have brought adverse environmental consequences to humankind like environmental pollution, the depletion of natural resources and global warming. Since the conventional solar panel is stationary and does not follow the direction of sunlight, it cannot obtain maximum sunlight intensity. Therefore, this project focuses on the design and development of solar charger which applies dual-axis solar tracking system by using Arduino Atmega328 microcontroller. The dual-axis tracker can track sunlight more effectively by aligning solar panel with the movement of the sun in order to allow the sunlight to fall perpendicularly onto the solar panel. The solar charger can automatically stop batteries charging when the batteries are charged to its maximum level. This microcontroller-based solar charger can track the sunlight more effectively than fixmounted solar panel to charge batteries to the maximum voltage efficiently.